Networking for Dummies 7th Edition - Lowe, Doug (Wiley Publishing, 2011)
This book helps you figure out whether you need a LAN at all--the author isn't shy about recommending simpler solutions such as printer switches--and then helps you get everything hooked up. Mainly, Lowe describes LANs in an accurate and comprehensive, though somewhat generic, way.